Efficiency and Social Inclusion: Implications for the Museum Profession (Cadernos de Sociomuseologia, 2012)
In the late 1980s Stephen Weil (1990) raised the question of the extent to which museum work could be considered a profession, the extent to which it had been professionalized, and in what ways this professionalization was facilitated or impeded by the changing circumstances of museum work, its organizational and governance context and its already multiplying roles vis-à-vis public culture and society at large. Although Weil‘s thoughts were situated in the American museum context of the mid-1980s, many of his thoughts apply to contexts beyond the US, and some of the questions he raised about the potential for professionalising museum work still resonate with the current situation of museum work. This paper tries to pose and approach a host of questions that, whilst in the main echoing Stephen Weil‘s mid-1980s reflections, are reconfigured in light of some sweeping changes in the nature of museum work, its mode of governance and its governing norms and values.